2013
DOI: 10.1080/17518253.2013.811298
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol as a promoting and recyclable medium for catalyst-free synthesis of linear thioethers: new antioxidants from eugenol

Abstract: We describe herein the use of glycerol as an efficient and recyclable solvent for the addition of thiols to nonactivated alkenes. The catalyst-free reactions take place easily using glycerol at room temperature or heating and the corresponding linear thioethers were obtained in good to excellent yields. The method was used to synthesize new sulfur-containing eugenols, which were tested for their antioxidant activities. The semisynthetic thio-derivatives were more effective in inhibition of induced lipid peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
(20 reference statements)
0
8
0
2
Order By: Relevance
“…Thionium 8 is then deprotonated to furnish the desired product ( 5 ) and regenerate pyridinium 9 . Such concerted hydrothiolation reactions of nonfluorinated alkenes has been previously suggested, though minimal experimental support exists for this mechanistic proposal. , Notably, this mechanism does not involve a β-F anionic intermediate that would typically decompose to deliver fluorovinylether side products.…”
Section: Results and Discussionmentioning
confidence: 84%
“…Thionium 8 is then deprotonated to furnish the desired product ( 5 ) and regenerate pyridinium 9 . Such concerted hydrothiolation reactions of nonfluorinated alkenes has been previously suggested, though minimal experimental support exists for this mechanistic proposal. , Notably, this mechanism does not involve a β-F anionic intermediate that would typically decompose to deliver fluorovinylether side products.…”
Section: Results and Discussionmentioning
confidence: 84%
“…However, the use of an initiator is not always necessary and sometimes the reaction can be performed by simple heating depending on the activation energy of the reaction between the alkene and the thiol. For instance, Lenardão et al 75 reported a method to functionalize eugenol with various aromatic thiols by thiol-ene coupling without any initiator and using glycerol as solvent. After 6 hours at 80 °C, moderate yields (57-67%) of thiol-ene coupling products were obtained, leading to various eugenol-based molecules with interesting antioxidant properties.…”
Section: Thiol-ene Reactionmentioning
confidence: 99%
“…It is used in perfumeries for its pleasant fragrance, as a flavoring agent in foods, as antiseptic and disinfectant in dental products and in many other fields [ 169 ]. Eugenol can be readily functionalized through the chemical transformation of the phenolic -OH group (mainly via the classical etherification and esterification reactions) [ 170 , 171 , 172 , 173 , 174 , 175 , 176 ], on the aromatic ring (through nitration reaction or Mannich bases formation) [ 177 , 178 , 179 , 180 ], as well as on the allylic functionality, through epoxidation [ 175 ] ( Figure 2 ).…”
Section: Monophenolsmentioning
confidence: 99%